Território e federação: a dimensão institucional da política regional da saúde no Rio Grande do Norte - Luciana da Costa Feitosa; Aldo Dantas (Confins)
The objective of this article is to analyze the institutional dimension of the geographical solidarity in the Sistema Único de Saúde, emphasizing the regional nature of the regulatory power of the norms through the apprehension and operationalization of the concepts of region and regionalization in the documents that subsidize health policy planning in the state of Rio Grande do Norte. Although regionalization has been considered as the structuring axis of SUS since the 1988 Constitution, the vertical normative propositions of the national federated entity and its weak management consolidation in the state federal entity are reflections of the complex organizational structure of the Brazilian federation, which "empties" the locus of regional power while it oscillates between the centralization of the national scale and the decentralization of the municipal scale, generating obstacles for the execution of a territorial pact of health policy.